Factors contributing to alcohol relapse in a rural population: Lessons from a camp-based de-addiction model from rural Karnataka - Rahul Rampure; Leeberk Raja Inbaraj; Carolin George Elizabeth; Gift Norman (Wolters Kluwer Medknow Publications, 2019)
Context: Alcohol consumption is the third largest risk factor for disease and disability in developing countries. Globally, 4% of all deaths are related to alcohol consumption every year. De-addiction measures and rehabilitation strategies can sometimes be challenging in rural population as there is a potential for a higher rate of relapse due to socio-cultural barriers such as unemployment, limited entrainment activities, and peer pressure during social events. Methodology: A cross-sectional study was conducted to determine the factors contributing to relapse in Bengaluru rural district. A total of 112 participants were interviewed, after attending de-addiction camp, using a semi-structured questionnaire containing instruments such as Penn Alcohol Craving Scale, self-efficacy scale, interpersonal support evaluation list, and presumptive stressful life events scale. Bivariate and multivariate logistic regression was done to determine the factors associated with relapse. Results: The relapse rate was 55.4% among the study participants. Education, self-efficacy, social support, and craving were associated with relapse in the bivariate analysis (P < 0.05). In multiple logistic regression model, craving (odds ratio [OR] - 1.8, confidence interval [CI]: 1.2-2.5), good interpersonal tangible support (OR - 0.09, CI: 0.01-0.5), and desirable life events (OR - 0.03, CI: 0.02-0.6) in the past were associated with relapse. Conclusion: Relapse rate was 55.4% among the study participants which is comparable to the findings of the other long-term studies. Increased craving, low-self-efficacy, and poor social support were associated with relapse hence need to be addressed in follow-up counseling sessions.